Dam Break Modelling and Flood Hazard Mapping for Cascading Dams in Sungai Perak Hydroelectric Scheme - Mohd Sidek L.; Yalit M.R.; Shah M.R.M.; Omar R.C.; Ahmed A.N.; Basri H.; Harun A. (Springer, 2023)
Detention of water by large barriers in dams creates lakes and reservoir. However, huge amount of water stored behind the dam can possess adverse effects to the downstream during the event of dam break. It is very much essential for executing dam break study as to provide possible flood inundation information and impact assessment to the dam. This study was conducted to carry out hydraulic and dam break analysis of the Temengor Dam PMF failure with chain reaction failure of Bersia, Kenering and Chenderoh Dams. Dam break modelling was performed under Probable Maximum Flood (PMF) scenario. MIKE 11 1-D model was used to derive breach outflow hydrograph, whereas MIKE 21 2-D model is being used for flood plain modelling and generation of inundations maps downstream of the dam. The routing of flow to the downstream area using MIKE Flood model was to obtain the flooded area, flood travel time and maximum flood depth. The breach outflow hydrographs for Temengor dam, Bersia dam, Kenering dam and Chenderoh dam yielded a peak value of 328,210m3/s, 216,366m3/s, 191,019m3/s and 112,277m3/s respectively. Based on the result, affected location or villages located at the downstream of the dam was determined. Indirectly, it will become as a reference for the agencies such as Jabatan Pertahanan Awam (JPAM) and Jabatan Bomba dan Penyelamat Malaysia to take safe precautions during the happening of unwilling disaster. 2020, Springer Nature Singapore Pte Ltd.